Nonlinear finite element analyses for the restoration study of Xana, Greece. (15th July 2018) - Terzi, Vasiliki G.; Ignatakis, Christos E.
Highlights: 3D finite element models of a monument produced by staged construction (initial and present state). Nonlinear static and dynamic analyses explain the monument's pathology. Large roof self-weight and absence of wooden tendons are the main pathology causes. Soil-structure interaction produces a more realistic finite element model. Restoration proposal refers to the use of pretensioned stainless steel tendons and partial reconstruction. Abstract: The object of the present research concerns the structural response of Xana, one of the earliest khans in the Balkan area, located in the archeological site of the municipality of Traianoupolis, Evros, Greece, due to static and seismic loading. The main research question is twofold: (a) what are the causes of nowadays structural pathology; and (b) what is the most adequate restoration scheme. The main methods used for the research refer to historical and bibliographical survey, experimental testing of the monument's materials and nonlinear numerical analyses conducted by the used of the finite element code ADINA. Therefore, two 3D nonlinear finite element models were constructed by the use of 'birth' and 'death' element option. The first model refers to the initial monument's stage till its current stage and the second model refers to its current stage till the restoration proposal. The results refer to the displacement field and failure figure due to static and dynamic loading, under the prism of a pushover analysis. Taking into account soil-structure interaction, the accurate structural geometry and staged construction proved to be essential for the correct estimation of the structural behavior. The absence of wooden tendons in combination with the large self-weight of the structure is the main reason of the monument's pathology. Therefore, the restoration proposal includes the construction of a light-weighted roof and the function of steel tendons.